Identity and access management: "Elevating security and efficiency: Unveiling the crucial aspects of identity and access management” - Saloni Kumari, (International Journal of Engineering and Technology, 2023)
The foundation of the software is the identity and access management system. A fundamental and essential cybersecurity competency is ensuring that the right parties have timely access to the right resources. The IAM has four domains: IAAA stands for identification, authentication, authorization, and accounting, the second is Privileged Access Management (PAM), third-party Identity Governance and Administration, data governance and protection. In this article, the concepts of identification, authentication, authorization, and accounting are discussed, as well as how IAAA works in an online setting.